In Memoriam Derrick Melville Dunlop LLD, MD, FRCP, FRCPEd, DSc, FACP FRCSEd(Hon), FDS, RCS(Hon). (Res Medica, 2014)
Sir Derrick Dunlop, Emeritus Professor of Therapeutics and Clinical Medicine at the University of Edinburgh and Honorary Fellow of the Royal College of Surgeons of Edinburgh died in Edinburgh on 19 June, 1980.To say of a man that he became a legend in his lifetime is to risk censure for inappropriate journalistic hyperbole, but when applied to Sir Derrick Dunlop this cliché acquires the dignity of simple truth. In the eyes of a generation of Edinburgh medical graduates he was indeed a legendary figure whose unique qualities as a teacher and as a clinician entitle him to an honoured place among the great names in the history of the Edinburgh Medical School.